2019
DOI: 10.1007/978-3-030-12346-8_69
|View full text |Cite
|
Sign up to set email alerts
|

Are We Training Our Novices Towards Quality 2D Profiles for 3D Models?

Abstract: In the history-based, feature-based, parametric CAD approach, 2D profile sketches are the basis for 3D models. Fully-constraining profiles is mandatory to create robust profiles. At present, neither CAD applications nor Model Quality Testing Tools usually check whether 2D profiles contain redundant constraints. Besides, our experience shows that novices tend to introduce redundant constraints. We hypothesize that 2D profiles over-constrained with redundant relations are more difficult to edit than those that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Rather, they have proven to be highly inefficient. Other studies [32] suggest that many users, even experts, often fail to use constraints in a robust and efficient manner that avoids redundant constraints. Other authors have recommended addressing the problem of constraint redundancy at the early stages of the learning process.…”
Section: Experimental Determination Of the Influence Of Redundant Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, they have proven to be highly inefficient. Other studies [32] suggest that many users, even experts, often fail to use constraints in a robust and efficient manner that avoids redundant constraints. Other authors have recommended addressing the problem of constraint redundancy at the early stages of the learning process.…”
Section: Experimental Determination Of the Influence Of Redundant Con...mentioning
confidence: 99%
“…Similarly, some proposals to homogenize and improve CAD assessment have been published [27][28][29][30] and various guidelines have been suggested to build 3D CAD models with design change capabilities [31]. However, research has shown that even expert users have difficulties identifying certain types of geometric constraints and determining whether a profile is fully constrained when no assistance is provided [32,33]. To the best of our knowledge, only a limited number of CAD tools provide some feedback to the user and implement mechanisms to manage the proliferation of redundant constraints.…”
Section: Introductionmentioning
confidence: 99%